Soil compaction in progressive agricultural tractor treads - Marques Filho, Aldir Carpes; Moura, Michel Dos Santos [UNESP]; Melo, André Campos [UNESP]; Damasceno, Fellippe Aaron [UNESP]; Lanças, Kléber Pereira [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Soil compaction is one of the main problems in world agriculture. It is known that, even in soil conservation management, such as in no-till, the transit of agricultural machinery damages the soil structure, therefore, it is essential to better understand the compaction processes and ways to alleviate the problem. In soils that have traditional tillage management, just one machine pass can damage the physical structure. This research aimed to evaluate the levels of compaction as a function of different passages of an agricultural tractor, considering the hypothesis that, during agricultural operations, a machine transits several times through the same place in the crop. The experiment was carried out on plowed and harrowed agricultural soil in the state of São Paulo. Resistance to soil penetration at different depths was evaluated, and the averages were correlated as a function of the number of steps taken by the tractor. Results showed that approximately 60% of the total soil compaction occurs in the first passes of the agricultural tractor, and above five passes the increase in compaction is minimal. At depths of 20 to 30 cm, the largest RSPs were found. It is concluded that a good planning of machinery traffic is essential, because in the case of a motor-mechanized set moving out of its predestined route, the soil structure is permanently affected.
Keywords: Cone index; Mechanization; Soil density